Microcontroller-Based Model Design of Automatic Center of Gravity and Ballast Measurements for MK Bomb Series - Piliang, Zuhnir; Lazuardi, Rudi; Hirawan, Agung (Talenta Publisher, 2025)
The determination of center of gravity (CG) of Mark 80 series bomb is crucial before being released from fighter-aircraft to reduce or eliminate bomb-pitching; thus, improving target accuracy. Current CG measurement in the service remains conventional, takes a long time, so the determination of ballast is guesswork, and the equipment used is not integrated. Therefore, this study aims to design a model of a microcontroller-based CG and ballast measuring instrument. This tool model uses two load cell sensors (as scales) to measure the weight of the bomb and two ultrasonic sensors to measure the distance between scales. The interface is LCD as digital output, keypad as ballast control and Arduino mega. The experimental method in this study employed test objects in the form of miniature MK 81 bombs and bomb-like test objects with known CG. A total of 6 types of tests obtained a tool accuracy rate of 99.2% with an accuracy of 2 mm. Given the efficiency and accuracy of the measurement, this model of CG and ballast measuring instrument can be a smart solution for military agencies to be used as an effective CG measuring tool for MK 80 bombs.